Revisiting consumer brand preference sustaining strategy through co-creation corporate social responsibility in the hospitality industry / Siti Hajar Md. Jani... [et al.] - Md. Jani, Siti Hajar; Ibrahim, Irwan; Amer, Afizan; Zulkifli, Nordayana; Ahmad, Mumtaz (Universiti Teknologi MARA, Negeri Sembilan, 2019)
When a hotel firm loses their existing customers, the organization needs to draw new customers. This is to maintain their market share in the industries. However, in order to attract and capture new customers, it may need higher cost on advertising and promotional activities. Brand preference is generally used to quantify the effect of brand equity that will lead to brand awareness and customers brand loyalty. Therefore, this research is conducted to examine how co-creation corporate social responsibility (CSR) influence brand preference sustaining strategy in the hospitality industry. The study involved three main variables to distinguish the effect of environment, society and stakeholders (CSR) base program on consumer brand preferences. This research is conducted at one of the hotels in Kuala Lumpur City. The scope of the research focusing on the impact of co-creation (CSR) programs towards consumer brand preference. The respondents are among the walk-in consumer the hotel. Result of the study found that there is significant impact of the three base (CSR) programs on consumer brand preference in the hotel industries. This study also built up a useful insight to the industry players and (CSR) research to gain knowledge on the future development of co-creation CSR programs which promotes low cost and high impact result.